Effectiveness of Pharmacist and Physician Collaboration in the Treatment of Type 2 Diabetes Mellitus With Severe Insulin Resistance Using U-500 Insulin. Issue 11 (November 2016) - Hess, Rick; Brandon, Sara; Johnson, Frank
Abstract : Objectives: To evaluate the effectiveness of pharmacist–physician collaboration in the treatment of type 2 diabetes mellitus (DM) with severe insulin resistance, using 500 U/mL concentrated regular insulin (U-500) in a primary care clinic that is not staffed by an endocrinologist. Methods: A retrospective chart review was conducted searching for patients who were prescribed U-500 insulin from January 1, 2008 through December 31, 2014. Subjects were included in the analysis if the pharmacist initiated U-500 insulin therapy, received treatment for at least 6 months, and who attended at least one follow-up visit with the pharmacist. Anyone who received U-500 insulin before the initial pharmacist consultation, managed by an endocrinologist, or who was missing follow-up hemoglobin A1c (HbA1c) laboratory values during the follow-up period was excluded. The primary endpoint was the change in HbA1c from U-500 initiation to 6 months later. Secondary endpoints included changes in weight, confirmed hypoglycemia events, changes in other anti-DM medications and the number of pharmacist and primary care physician visits during the follow-up period. Results: Eighty-one patients were identified and screened, and 44 patients were included in the analysis. Baseline HbA1c (mean ± standard deviation) was 9.7% ± 1.6% and decreased to 8.6% ± 1.6% after 6 months of follow-up, representing a reduction of 1.1% (95% confidence interval −1.6 to −0.6, P < 0.001). Body weight increased (mean ± standard deviation) by 6.7 ± 15.1 lb from baseline ( P = 0.005). The frequency of confirmed hypoglycemia events was low (0.8 events per patient). Treatment with metformin was preserved, whereas most other DM medications were discontinued. A similar number of pharmacist and physician follow-up visits were completed by the end of the study period (2.0 and 2.7 visits, respectively; P = 0.805). Conclusions: Initiation of U-500 insulin by clinical pharmacists collaborating with primary care physicians results in improved DM control in patients with severe insulin resistance. Our findings suggest this interprofessional partnership provides an alternative referral approach for primary care physicians when endocrinology services are absent or limited. Abstract : The burden of treating diabetes mellitus (DM) weighs more heavily on primary care physicians because a shortage of endocrinologists exists in the United States, and as a result fewer referral opportunities are available. Pharmacists are allied team members who can provide medication therapy management services. This article provides a review of the clinical efficacy of an interprofessional collaboration using pharmacists in a primary care setting to assist in the treatment of patients with type 2 diabetes mellitus with severe insulin resistance.